An Ascending Aortic Thrombus - Egbe, Antoine; Tadesse, Eyouab; Ruffino, Catrina; Arshad, Khurram; Sandio, Aubin; Mozaffari, Ali; Subahi, Ahmed; Jamil, Mariam; Tynes, Donald; Delafontaine, Patrice (Cardiology and Cardiovascular Medicine, 2024)
An ascending aortic thrombus is a rare finding, but it is a widely known cause of systemic embolization. Our case presents a 50-year-old man who presented with acute mesenteric ischemia. This was the result of a peripheral embolism originating from the ascending aortic thrombus. There was no pre-existing clotting abnormality. Conservative treatment with apixaban was initially tried since the patient was deemed not to be a suitable surgical candidate. However, the patient did not adhere to treatment. He later presented to the emergency department with severe abdominal pain and was found to have numerous embolic lesions to various body organs comorbid to his acute mesenteric ischemia. Only a few cases of intra-aortic thrombus without any coagulation abnormality are described in the literature. Occasionally, they present as acute mesenteric ischemia. We write about this case to emphasize its existence and highlight the serious morbidity and mortality associated with systemic embolization as a result of an intra-aortic thrombus.